Dietary quality among men and women in 187 countries in 1990 and 2010: a systematic assessment - Dr. Fumiaki Imamura, PhD; Renata Micha, PhD; Shahab Khatibzadeh, MD; Saman Fahimi, MD; Peilin Shi, PhD; John Powles, MBBS; Dariush Mozaffarian, DrPH (Elsevier, 2015)
Background: Healthy dietary patterns are a global priority to reduce non-communicable diseases. Yet neither worldwide patterns of diets nor their trends with time are well established. We aimed to characterise global changes (or trends) in dietary patterns nationally and regionally and to assess heterogeneity by age, sex, national income, and type of dietary pattern. Methods: In this systematic assessment, we evaluated global consumption of key dietary items (foods and nutrients) by region, nation, age, and sex in 1990 and 2010. Consumption data were evaluated from 325 surveys (71·7% nationally representative) covering 88·7% of the global adult population. Two types of dietary pattern were assessed: one reflecting greater consumption of ten healthy dietary items and the other based on lesser consumption of seven unhealthy dietary items. The mean intakes of each dietary factor were divided into quintiles, and each quintile was assigned an ordinal score, with higher scores being equivalent to healthier diets (range 0-100). The dietary patterns were assessed by hierarchical linear regression including country, age, sex, national income, and time as exploratory variables. Findings: From 1990 to 2010, diets based on healthy items improved globally (by 2·2 points, 95% uncertainty interval (UI) 0·9 to 3·5), whereas diets based on unhealthy items worsened (−2·5, −3·3 to −1·7). In 2010, the global mean scores were 44·0 (SD 10·5) for the healthy pattern and 52·1 (18·6) for the unhealthy pattern, with weak intercorrelation (r=-0·08) between countries. On average, better diets were seen in older adults compared with younger adults, and in women compared with men (p<0·0001 each). Compared with low-income nations, high-income nations had better diets based on healthy items (+2·5 points, 95% UI 0·3 to 4·1), but substantially poorer diets based on unhealthy items (−33·0, −37·8 to −28·3). Diets and their trends were very heterogeneous across the world regions. For example, both types of dietary patterns improved in high-income countries, but worsened in some low-income countries in Africa and Asia. Middle-income countries showed the largest improvement in dietary patterns based on healthy items, but the largest deterioration in dietary patterns based on unhealthy items. Interpretation: Consumption of healthy items improved, while consumption of unhealthy items worsened across the world, with heterogeneity across regions and countries. These global data provide the best estimates to date of nutrition transitions across the world and inform policies and priorities for reducing the health and economic burdens of poor diet quality. Funding: The Bill & Melinda Gates Foundation and Medical Research Council.